A wearable wrist haptic display for motion tracking and force feedback in the operational space. (14th May 2021) - Laghi, Marco; Catalano, Manuel G.; Grioli, Giorgio; Bicchi, Antonio
Abstract: Force feedback is often beneficial for robotic teleoperation, as it enhances the user's remote perception. Over the years, many kinesthetic haptic displays (KHDs) have been proposed for this purpose, which have different types of interaction and feedback, depending on their kinematics and their interface with the operator, including, for example, grounded and wearable devices acting either at the joint or operational space (OS) level. Most KHDs in the literature are for the upper limb, with a majority acting at the shoulder/elbow level, and others focusing on hand movements. A minority exists which addresses wrist motions. In this paper, we present the Wearable Delta (W $ Δ $ ), a proof-of-concept wearable wrist interface with hybrid parallel–serial kinematics acting in the OS, able to render a desired force directly to the hand involving just the forearm–hand subsystem. It has six degrees of freedom (DoFs), three of which are actuated, and is designed to reduce the obstruction of the range of the user's wrist. Integrated with positions/inertial sensors at the elbow and upper arm, the W $ Δ $ allows the remote control of a full articulated robotic arm. The paper covers the whole designing process, from the concept to the validation, as well as a multisubject experimental campaign that investigates its usability. Finally, it presents a section that, starting from the experimental results, aims to discuss and summarize the W $ Δ $ advantages and limitations and look for possible future improvements and research directions.